Peningkatan Pengetahuan Kesiapsiagaan Kegawatdaruratan Jantung melalui Edukasi Kesehatan pada Masyarakat Dewasa di Puskesmas Suka Indah - Vidya Urbaningrum; Muhammad Ifadh Arifqy Jayusman; Suanda Saputra; Eli Ermawati; Luh Ade Lela Arika; Apina Apina; Rama Nafil Hidayat; Yulfa Yulfa; Sri Rahayu Nabilameysadin (Civiliza Publishing, 2025)
(1) Background: Health problems that are not caused by infection, especially heart and blood vessel problems, remain the main reason people die and experience medical emergencies in our environment. Because people lack understanding and are not prepared to face critical situations related to the heart, this can result in first treatment being delayed.. (2) Research Objective: This activity aims to assess the effectiveness of health education in increasing knowledge of cardiac emergency preparedness in the adult community in the Suka Indah Community Health Center working area.; (3) Method: Community service activities use a pre-test and post-test design without a control group. Health education is provided through interactive lectures, discussions and video media. Evaluation was carried out using a knowledge questionnaire for 40 respondents before and after education. (4) Results: The pre-test results showed that the majority of respondents had a level of knowledge in the poor category (75%). After being given education, there was an increase in knowledge, shown by the increase in respondents in the good category to 82.5% and there were no more respondents with poor knowledge. (5) Conclusion: Health education is effective in increasing public knowledge regarding cardiac emergency preparedness and can be a promotive-preventive strategy in primary health services.